EFFORTS TO INCREASE TEACHER ABILITY IN MAKING LEARNING VIDEOS THROUGH WORKSHOP - Septina Katrin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The background of this research is the number of teachers who teach using conventional learning methods without utilizing technological developments. The researcher strives to run workshops to increase teachers’ ability in making learning videos. This research was a classroom action research conducted on teachers of SDN 006 Mandau in the odd semester of 2019–2020. The instrument used was an observation sheet. The results of the study showed that in the first cycle, the percentage of teachers’ ability in making learning videos was 56.24%, categorized as medium. After improvements, in cycle II it increased to 76.03%, which is categorized as high. Based on the results of the study, it can be concluded that the ability of teachers in making learning videos has increased through workshops.